A comparison on efficiency of domestic and foreign banks in Malaysia: a DEA approach - Ong, Tze San; Lim, Yee Theng; Teh, Boon Heng (Society of Business and Management Dynamics, 2011)
This study utilizes non parametric Data Envelopment Analysis (DEA) to analyze and compare the efficiency of foreign and domestic banks in Malaysia. The analysis is based on a panel data set of 9 domestic banks and 12 foreign banks in Malaysia over the period of 2002 - 2009. Intermediation approach is used to define the inputs and outputs in computerizing the efficiency scores. Surprisingly, the findings are inconsistent with most of the findings of previous studies where the foreign banks were outperforming their domestic peers in term of efficiency. Conversely, the finding of this study shows that domestic banks have a higher efficiency level than foreign banks, this imply that domestic banks are relatively more managerially efficient in controlling their costs. The second stage of the empirical results is based on the Tobit model, which suggests that the pure technical efficiency (PTE) of banks in Malaysia is mainly affect by capital strength, loan quality, expenses and asset size.